Transformasi Teknologi Dan Kepemimpinan Terhadap Organizational Agility: Peran Mediasi Dynamic Capabilities Pada Umkm Halal - Sri Ernawati; Andre Dwijanto Witjaksono; Anamg Kistyanto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The growth of the global halal industry presents significant opportunities for halal SMEs in Indonesia, particularly in West Nusa Tenggara Province (NTB). However, challenges in enhancing organizational agility remain a major obstacle amid the ever-changing market dynamics. This study aims to analyze the influence of technological transformation and leadership on the agility of halal SMEs, with dynamic capabilities as a mediating variable. A quantitative approach was employed through an explanatory survey method, involving 100 halal-certified SMEs in Bima City, Bima Regency, and Dompu Regency, selected using purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with Structural Equation Modelling (SEM) using SmartPLS software. The results of the study show that technological transformation and leadership, with dynamic capabilities as a mediating variable, have a positive and significant effect on the agility of halal MSMEs.